Barriers to environmental sustainability of construction projects. Issue 4 (2nd September 2019) - Opoku, De-Graft Joe; Ayarkwa, Joshua; Agyekum, Kofi
Abstract : Purpose: The construction industry plays an important role in the achievement of the 11th and 15th of the Sustainable Development Goals. Efforts have been made by most developing and developed economies toward the achievement of these goals. Despite the efforts being made by the construction industry toward the achievement of these goals, there are still barriers that prevent built environment consultants from advancing environmental sustainability (ES) of construction projects. The purpose of this paper is to identify barriers to ES of construction projects. Design/methodology/approach: An extensive literature review on barriers to the adoption of ES was conducted and face-to-face semi-structured interviews of purposively selected built environment consultants in Ghana were carried out. Thematic template analysis of qualitative data was conducted. Findings: The key findings from the study include perceived initial costs, lack of knowledge on ES, technological difficulties, external pressures in adopting ES practices and environmental conditions in developing countries. Originality/value: The outputs of this study offer strategies which are very significant to the construction industry in embracing ES. Further, the findings contribute to knowledge on achieving the sustainable development agenda.